AKSES MASYARAKAT MISKIN TERHADAP PELAYANAN JAMINAN KESEHATAN DAERAH (JAMKESDA) DI KOTA PEKANBARU - Atsmana, Najibardhi; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Health is one of the precious human needs. Where health has a value that is very expensive.All human activities of waking, working, sleeping and awake back-related effect on health.free heath program for the poor seems very realitis and so need to be implemented by each region in homeland.health factor is an integral part of the lives of the poor. Breakthrough local governments both at the provincial, district/city level, health conters provide free health checks kospitalization, community health centers, and community health posts is also a good first step and needs to be retained.in fact, there are some areas that have been exempt up in the level of care in hospitals. This study aims to determine the response of the poor to heath services made by the government and to determine the factors causing low health insurance program area. Type of research is a qualitative research based on the picture of the situation and is generally referred to pendeskripsian or descriptive analysis. Data collection techniques researchers study conducted by observation and interviews. The results show that the public response to regional health assistance program designed specifically for the poor. In this case also to be positive and negative. While the low factor jamkesda program is that where as for the government’s efforts to tackle the problem by finding appropriate solutions shared expectations.through this study suggested that the desire or expectation or respondents or participants can be met with good jamkesda. In accordance with the shared expectations.Keywords :Access, Health services, and Poverty